2015
DOI: 10.1371/journal.pone.0132531
|View full text |Cite|
|
Sign up to set email alerts
|

Stronger Neural Modulation by Visual Motion Intensity in Autism Spectrum Disorders

Abstract: Theories of autism spectrum disorders (ASD) have focused on altered perceptual integration of sensory features as a possible core deficit. Yet, there is little understanding of the neuronal processing of elementary sensory features in ASD. For typically developed individuals, we previously established a direct link between frequency-specific neural activity and the intensity of a specific sensory feature: Gamma-band activity in the visual cortex increased approximately linearly with the strength of visual moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 80 publications
2
19
0
Order By: Relevance
“…Interestingly, these visual and attentional mechanisms have all been reported to be anomalous in ASD in previous behavioral studies (for reviews see Dakin and Frith, 2005;Simmons et al, 2009;Keehn et al, 2013Robertson and Baron-Cohen, 2017). Overall, these results suggest that beta oscillations might be a relevant target for neurophysiological studies testing altered neural oscillations during visual processing in ASD, similarly to what have been recently shown for gamma band oscillations (Sun et al, 2012;Peiker et al, 2015) and alpha-gamma coupling (Seymour et al, 2019). and attentional tasks, including crowding, in the present study we employed high-density electroencephalography (EEG) in participants with ASD to investigate the neurophysiological (ERPs) and oscillatory correlates of local visual processing within a crowding regime, and to study the underlying network activity and connectivity pattern at the level of cortical sources.…”
Section: Introductionsupporting
confidence: 70%
“…Interestingly, these visual and attentional mechanisms have all been reported to be anomalous in ASD in previous behavioral studies (for reviews see Dakin and Frith, 2005;Simmons et al, 2009;Keehn et al, 2013Robertson and Baron-Cohen, 2017). Overall, these results suggest that beta oscillations might be a relevant target for neurophysiological studies testing altered neural oscillations during visual processing in ASD, similarly to what have been recently shown for gamma band oscillations (Sun et al, 2012;Peiker et al, 2015) and alpha-gamma coupling (Seymour et al, 2019). and attentional tasks, including crowding, in the present study we employed high-density electroencephalography (EEG) in participants with ASD to investigate the neurophysiological (ERPs) and oscillatory correlates of local visual processing within a crowding regime, and to study the underlying network activity and connectivity pattern at the level of cortical sources.…”
Section: Introductionsupporting
confidence: 70%
“…These results are also intriguing in the context of a recent finding of increased inter-trial variability in ASD (Dinstein et al, 2012 ). Unmodulated, i.e., inconsistently gain controlled, feedforward inputs, as observed previously in ASD (Peiker et al, 2015 ), would likely result in more variable trial to trial onset responses. Lastly, these results are also relevant in the context of the high prevalence of behavioral sensory hypo- and hyper- sensitivities in ASD (Tommerdahl et al, 2007 ; Marco et al, 2011 , 2012 ).…”
Section: Discussionmentioning
confidence: 72%
“…Reduced gamma coherence in the visual cortex was also reported by Peiker et al (2015a), who utilised a paradigm requiring the identification of moving objects presented through a narrow slit, necessitating the integration of perceptual information across time. However, another study by the same group, reported greater modulation of total gamma power in response to visual motion intensity for ASD participants (Peiker, Schneider, et al, 2015b).…”
Section: Introductionmentioning
confidence: 91%